2010
DOI: 10.1021/jf904062c
|View full text |Cite
|
Sign up to set email alerts
|

Coffee and Caffeine Ameliorate Hyperglycemia, Fatty Liver, and Inflammatory Adipocytokine Expression in Spontaneously Diabetic KK-Ay Mice

Abstract: Epidemiological surveys have demonstrated that habitual coffee consumption reduces the risk of type 2 diabetes. The aim of this work was to study the antidiabetic effect of coffee and caffeine in spontaneously diabetic KK-A(y) mice. KK-A(y) mice were given regular drinking water (controls) or 2-fold diluted coffee for 5 weeks. Coffee ingestion ameliorated the development of hyperglycemia and improved insulin sensitivity. White adipose tissue mRNA levels of inflammatory cytokines (MCP-1, IL-6, and TNFalpha), ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
68
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 37 publications
3
68
0
Order By: Relevance
“…Chronic coffee consumption has been reported to have similar effects [30]. On the other hand, coffee can impair insulin sensitivity, while liver steatosis and inflammation is reduced, despite identical and unchanged body weight in spontaneously diabetic mice [31]. Thus, L-RISK and H-RISK diets are likely to improve insulin sensitivity by different mechanisms, which may occur independently of the weight loss resulting from energy restriction.…”
Section: Discussionmentioning
confidence: 97%
“…Chronic coffee consumption has been reported to have similar effects [30]. On the other hand, coffee can impair insulin sensitivity, while liver steatosis and inflammation is reduced, despite identical and unchanged body weight in spontaneously diabetic mice [31]. Thus, L-RISK and H-RISK diets are likely to improve insulin sensitivity by different mechanisms, which may occur independently of the weight loss resulting from energy restriction.…”
Section: Discussionmentioning
confidence: 97%
“…In another experiment, we showed that coffee or caffeine ingestion prevented the development of glucose intolerance and insulin resistance in C57BL/6J mice fed a high-fat diet for 17 wk (5). In KK-A y mice, the accumulation of triglycerides in liver was reduced by coffee ingestion (4). As fatty liver provokes insulin resistance in liver, coffee might decrease insulin resistance in liver by ameliorating fatty liver.…”
mentioning
confidence: 96%
“…We recently examined the anti-diabetic effect of coffee using KK-A y mice, a type 2 diabetes animal model, and demonstrated that coffee or caffeine ingested as drinking water ameliorated hyperglycemia, insulin resistance, and fatty liver in those mice (4). In another experiment, we showed that coffee or caffeine ingestion prevented the development of glucose intolerance and insulin resistance in C57BL/6J mice fed a high-fat diet for 17 wk (5).…”
mentioning
confidence: 99%
“…It was reported that caffeine might also improve insulin sensitivity and fatty liver in mice. 28) In addition, coffee and caffeine can cause weight loss, 29,30) possibly reducing visceral fat and thereby reducing lipid accumulation in hepatocytes. Of all the types of fat tissue, visceral fat is the most metabolically active and which plays an important role in the development of fatty liver.…”
Section: Discussionmentioning
confidence: 99%